Connecting the real world with the ubiquitous overlay in ambient media - Lugmayr, Artur (2009)
Ambient media (as synonymous for 'ubiquitous media') are proactive media objects embedded into the natural human environment by recognizing the context of the consumer. A few prominent examples are location based services, implicit personalization, or gesture based human-computer interfaces. More advanced examples have been contributed to the yearly Nokia Ubimedia MindTrek Award (see [1, 2]), or presented during the SAME workshop series (see [3, 4]). Ambient content therefore can be described as ubiquitous overlay of the real physical world. This keynote especially addresses the general notion of ambient media, as based on the research works presented in [5-7]. However, the keynote especially devotes to the question, how the ubiquitous overlay can be connected to the real world. To realize proactive ubiquitous system, the digital overlay can be described as 'digital mind' distributed in time and space over the real world happenings. The ubiquitous system recognizes context, state of human mind, situations, and media system events to be able to react smartly on signaling input. The aim of this keynote is to present context awareness as one of the challenges in ubiquitous system. As an extension to the thoughts presented in [8], context awareness can be described as a system with the capability to explore the temporal/spatial changes in an environment and react to changes autonomously within specific application domains. The idea of this keynote is to merge the ideas of context awareness with the idea of modeling events in multimedia systems (see [9]). Thus, how the digital overlay can be connected to the real-world state based on sensory input modeled as events. One of the current trends is the creation of ontologies for events in multimedia systems. Due to the fact, that many multimedia systems can be modeled as cause-effect relationships linked via event-alike connections (e.g. distributed emergency response systems [9]). Thus they keynote presents how the ubiquitous digital overlay can be linked to the physical world by using 'context aware events'. A few practical examples of existing projects are presented, and shall enrich the keynote with a more application oriented approach.